Rural development thinking, moving from the green revolution to food sovereignty (2016)
Since the middle of the last century, several perspectives have addressed rural development from different viewpoints, and productive aspects have prevailed. Four general approaches encompass these perspectives: the Technocratic, Sociological, Socio-Technocratic, and Political approaches. This paper aims to put forward Food Sovereignty and its focus on the rights of rural inhabitants as a perspective of the political approach to rural development. Despite the fact that food sovereignty integrates important topics such as the recognition of the importance of rural inhabitants by society, it is necessary to make a clear proposal for how to incorporate consumers in its postulates.